InvestiGators - Ants in Our P.A.N.T.S. - Book 4 Ants in our P.A.N.T.S. - Green, John, 1975-; Dzioba, Wes (New York : First Second, 2021)
"With agent Brash trapped in a mysterious coma, the technicians at S.U.I.T. have designed the ultimate replacement: RoboBrash. This high-tech replica has been programmed with all of the original Brash's crime-fighting skills and knowhow--but it seems he's got a few bugs in his system. Will Mango and his new partner be enough to stop the giant ants that are on a rampage in the city?"--Provided by publisher.
Keywords: Alligators -- Comic books, strips, etc; Private investigators -- Comic books, strips, etc; Ants -- Comic books, strips, etc; Alligators -- Fiction; Private investigators -- Fiction; Ants -- fiction; Funny animal comics; Humorous comics; Detective and mystery comics; Graphic novels